Nivolumab and Ipilimumab as Maintenance Therapy in Extensive-Disease Small-Cell Lung Cancer: CheckMate 451. Issue 12 (20th April 2021) - Owonikoko, Taofeek K.; Park, Keunchil; Govindan, Ramaswamy; Ready, Neal; Reck, Martin; Peters, Solange; Dakhil, Shaker R.; Navarro, Alejandro; Rodríguez-Cid, Jerónimo; Schenker, Michael; Lee, Jong-Seok; Gutierrez, Vanesa; et al.
Abstract : PURPOSE: In extensive-disease small-cell lung cancer (ED-SCLC), response rates to first-line platinum-based chemotherapy are robust, but responses lack durability. CheckMate 451, a double-blind phase III trial, evaluated nivolumab plus ipilimumab and nivolumab monotherapy as maintenance therapy following first-line chemotherapy for ED-SCLC. METHODS: Patients with ED-SCLC, Eastern Cooperative Oncology Group performance status 0-1, and no progression after ≤ 4 cycles of first-line chemotherapy were randomly assigned (1:1:1) to nivolumab 1 mg/kg plus ipilimumab 3 mg/kg once every 3 weeks for 12 weeks followed by nivolumab 240 mg once every 2 weeks, nivolumab 240 mg once every 2 weeks, or placebo for ≤ 2 years or until progression or unacceptable toxicity. Primary end point was overall survival (OS) with nivolumab plus ipilimumab versus placebo. Secondary end points were hierarchically tested. RESULTS: Overall, 834 patients were randomly assigned. The minimum follow-up was 8.9 months. OS was not significantly prolonged with nivolumab plus ipilimumab versus placebo (hazard ratio [HR], 0.92; 95% CI, 0.75 to 1.12; P = .37; median, 9.2 v 9.6 months). The HR for OS with nivolumab versus placebo was 0.84 (95% CI, 0.69 to 1.02); the median OS for nivolumab was 10.4 months. Progression-free survival HRs versus placebo were 0.72 for nivolumab plus ipilimumab (95% CI, 0.60 to 0.87) and 0.67 for nivolumab (95% CI, 0.56 to 0.81). A trend toward OS benefit with nivolumab plus ipilimumab was observed in patients with tumor mutational burden ≥ 13 mutations per megabase. Rates of grade 3-4 treatment-related adverse events were nivolumab plus ipilimumab (52.2%), nivolumab (11.5%), and placebo (8.4%). CONCLUSION: Maintenance therapy with nivolumab plus ipilimumab did not prolong OS for patients with ED-SCLC who did not progress on first-line chemotherapy. There were no new safety signals.